Integration of anatomy and physiology into nursing practice as perceived by undergraduate students and registered nurses: a scoping review - Miwa Horiuchi-Hirose; Tomoko Fukuoka; Yuka Saeki (BMC, 2023)
Abstract Objective The current study aimed to determine perceptions of registered and student nurses regarding the integration of anatomy and physiology into nursing practice. Methods This scoping review was conducted following the checklist provided in the Reporting Items for Systematic reviews and Meta-Analysis extension for scoping reviews. Articles published in PubMed, ERIC, and CINAL from January 1, 2002 to September 30, 2022 were included. Results A literature review of 20 articles that matched the indicative criteria revealed that both undergraduate student and registered nurses recognized knowledge of anatomy and physiology as important to nursing practice. Student nurses recognized that such knowledge is related to understanding patient pathophysiology, patient observation, treatment selection, and patient safety and forms the basis for nursing practice. Registered nurses who were confident in their knowledge of anatomy and physiology also reported that they were able to explain the rationale for their nursing practice. They also reported that this knowledge is necessary for communication with multiple professions, which promotes patient/family trust in nurses and is the basis for building trusting relationships with patients and their families. Conclusions Although undergraduate student and registered nurses recognized the importance of learning anatomy and physiology, the integration of anatomy and physiology into nursing practice was not the same for all student and registered nurses. This suggests the need to investigate the overall perceptions of nurses regarding the integration of anatomy and physiology into nursing practice and for faculty to discuss how to facilitate critical thinking among students.